Сучасний стан родючості чорноземних ґрунтів та шляхи підвищення продуктивності сільськогосподарських культур - Кобець, Анатолій Степанович; Kobets, Anatolii; Грицан, Юрій Іванович; Gritsan, Yurii; Крамарьов, С. М.; Kramar’ov, S.; Мицик, Олександр Олександрович; Mytsyk, Oleksandr (Дніпровський державний аграрно-економічний університет, 2016)
В останні десятиріччя продукція рослинництва формується головним чином на залишкових запасах елементів живлення та мінералізації гумусу. Така ситуація викликана зменшенням обсягів внесення добрив, порушенням сівозмін та насиченням їх просапними культурами, зокрема соняшником. Ці й інші фактори спричинюють поширення і розвиток ерозії, дегуміфікацію, агрохімічну і агрофізичну деградацію з втратою агрономічно цінної структури і погіршують фізичні й водні властивості чорноземних ґрунтів. Внесення незбалансованих, переважно азотних мінеральних добрив веде до вилуговування основ, збіднення ґрунтового вбирного комплексу та зниження його буферної здатності. У найбільш родючих ґрунтах – чорноземах – підвищується гідролітична кислотність, що вказує на потенційну небезпеку подальшої деградації цих ґрунтів. Одним із шляхів вирішення проблеми відновлення втраченої родючості чорноземних ґрунтів є впровадження у виробництво сучасних технологій вирощування сільсько-господарських культур з мінімалізацією обробітку ґрунту та елементами біологізації землеробства.The current state of fertility of black soils and the ways of its increase were studied. In modern conditions the resumption of agricultural production and increase the fertility of chernozem soils is a very important issue of agriculture. This is due to the fact that the black soil that previously relatively rich on mobile forms of nutrients lost its former high natural fertility as a result of their long inefficient usage and they are no longer able to provide the necessary quantity of agricultural plant nutrients. In the last decade crop production is mainly formed by the residual reserves of nutrients and humus mineralization. This consequences, which caused a decrease in the volume of fertilizer application, crop rotation and breach of saturation of cultivated crops, particularly sunflower. As a result, they contribute to the spread and development of erosion, dehumification, agrochemical and agrophysical degradation with the loss of agronomically valuable structure and deterioration of the physical properties of black soils. Using of unbalanced, primarily nitrogen fertilizer leads to leaching of calcium compounds from the soil, depletion of soil-absorbing complex of nutrients and reducing soil buffering. One way to solve the problem of renewal of the lost fertility of these soils is the introduction of modern technologies in growing crops that minimize tillage and agriculture biologization elements. It is necessary to restore the lost fertility of our soils and black soil to create a model of our soil and land management system and Ukrainewill take place in the global market as a de-veloped agricultural country and a reliable eksporter food raw materials.
The current state of fertility of black soils and ways to increase the productivity of crops
Keywords: ґрунт; soil fertility; деградація; degradation; сучасні технології; modern technology; агрохімічні показники; agrochemical indices; врожай; yield; якість продукції; quality